Anti-Inflammation Property of Syzygium cumini (L.) Skeels on Indomethacin-Induced Acute Gastric Ulceration - Lanchakon Chanudom; Jitbanjong Tangpong (Gastroenterology Research and Practice)
Indomethacin, nonsteroidal anti-inflammatory drug (NSAIDs), induced gastric damage and perforation through the excess generation of reactive oxygen species (ROS). Syzygium cumini (L.) Skeels is commonly used as a medicinal plant and is claimed to have antioxidant activities. The effects of Syzygium cumini (L.) Skeels aqueous extract (SCC) on antifree radical, anti-inflammation, and antiulcer of SCC on indomethacin induced acute gastric ulceration were determined in our study. Scavenging activity at 50% of SCC is higher than ascorbic acid in in vitro study. Mice treated with indomethacin revealed mucosal hemorrhagic lesion and inhibited mucus content. Pretreatment with SCC caused discernible decrease in indomethacin induced gastric lesion and lipid peroxide content. In addition, oxidized glutathione (GSSG), glutathione peroxidase (GPx), nitric oxide (NO) levels, and gastric wall mucus were restored on acute treated mice model. Indomethacin induced inflammation by activated inducible nitric oxide synthase (iNOS) and tumor necrosis factor-alpha (TNF-α) proinflammatory cytokines to release large amount of ROS/RNS which were ameliorated in mice pretreatment with SCC. SCC showed restoration of the imbalance of oxidative damage leading to amelioration of cyclooxygenase enzyme (COX). In conclusion, SCC acts as an antioxidant, anti-inflammation, and antiulcer against indomethacin.